2020
DOI: 10.1302/2633-1462.110.bjo-2020-0133.r1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the COVID-19 lockdown on hand trauma surgery utilization

Abstract: Aims The aim of this study was to evaluate the need for hand trauma services during the COVID-19 pandemic lockdown, specifically related to surgical requirements. This will provide useful information for planning and resource allocation in the event of any further lockdown. Methods A prospective analsysis of all patients attending our hand trauma unit throughout the UK COVID-19 lockdown period (24 March to 10 May 2020) was carried out. Prospectively collected departmental data from the same period in 2019 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
2
24
1
Order By: Relevance
“…These findings are reflected in other studies examining hand trauma during the COVID-19 pandemic. 19 , 25 Discourse looking at the specific activity implicated have suggested that sports related trauma was reduced whilst domestic ‘do-it-yourself’ (DIY) injuries and injuries related to deliberate self-harm (DSH) were more prevalent. 19 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…These findings are reflected in other studies examining hand trauma during the COVID-19 pandemic. 19 , 25 Discourse looking at the specific activity implicated have suggested that sports related trauma was reduced whilst domestic ‘do-it-yourself’ (DIY) injuries and injuries related to deliberate self-harm (DSH) were more prevalent. 19 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…Along with the WHO interim guidance, this finding indicates that inpatient admission processes may need to be adjusted as the risks and benefits of hospital-based care change suggest that inpatient admission processes may need to be modified [25]. Other studies from many countries also uncovered a decrease in patient's length of stay due to pandemic [26], [27]. Discharge planning coordinated with primary care follow-up can also help to shorten hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…35 , 36 The majority of studies were based in urban locations, with heavy bias towards high-income countries, including the United States (n = 14), 17 , 18 , 19 , 22 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 37 , 38 , 39 Australia (n = 2), 23 , 34 and Western Europe (n = 18). 20 , 21 , 24 , 26 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 Records were examined visually via placement of study results onto a world map. All eight studies showing an increase in violence were based in the United States.…”
Section: Methods Of Studymentioning
confidence: 99%